2004
DOI: 10.1038/sj.bjc.6602234
|View full text |Cite
|
Sign up to set email alerts
|

Endostatin expression in pancreatic tissue is modulated by elastase

Abstract: Pancreatic tumours are scirrhous, avascular tumours, suggesting that they may produce angiogenesis inhibitors that suppress the growth of the vasculature to the tumour and metastases. We have sought evidence for the angiogenesis inhibitor, endostatin, in normal and cancerous pancreatic tissue. Using Western blotting, we found mature 20 kDa endostatin in cancer tissue but not in normal tissue. Several endostatin-related peptides of higher mol wt were present in both tissues. Extracts from normal tissue were abl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…This compares with the Km of 1.1 mM for an elastase we identified in human pancreas (Brammer et al, 2005) and human leukocyte elastase where the Km is reported to be 0.14 mM (Castillo et al, 1979). Effect of TNFa on endostatin production from SUIT-2 cells Figure 6 shows the effect of incubation of SUIT-2 cells with TNFa for 48 h on endostatin secretion.…”
Section: Elastase Activity In Suit-2 Cellsmentioning
confidence: 60%
See 3 more Smart Citations
“…This compares with the Km of 1.1 mM for an elastase we identified in human pancreas (Brammer et al, 2005) and human leukocyte elastase where the Km is reported to be 0.14 mM (Castillo et al, 1979). Effect of TNFa on endostatin production from SUIT-2 cells Figure 6 shows the effect of incubation of SUIT-2 cells with TNFa for 48 h on endostatin secretion.…”
Section: Elastase Activity In Suit-2 Cellsmentioning
confidence: 60%
“…Although they may have a role in endostatin generation , they may also be important in endostatin degradation. We previously implicated elastase in the degradation of endostatin in extracts of normal pancreas (Brammer et al, 2005). The release of intracellular proteases that degrade endostatin following tissue injury, may be a means to reduce local endostatin levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Now that at least one inhibitor of endostatin is known, it may also be possible to modify the amino-acid sequence of endostatin to create analogues, which retain antiangiogenic activity but which are more resistant to degradation by pancreatic elastase. One issue which was not addressed by the study by Brammer et al (2005) is whether any products of endostatin resulting from elastase digestion retain activity as inhibitors of angiogenesis. Adenocarcinoma of the pancreas has largely frustrated the efforts of oncologists to modify its behaviour.…”
mentioning
confidence: 99%